The role of youth victimization trauma on the interpersonal reactivity - Fonseca, Ana R. (2019)
Poster presented at the 4th International Congress of CiiEM – “Health, Well-being and Ageing in the XXI Century.” 2-5 June 2019, Campus Egas Moniz, Monte de Caparica, Portugal